2003
DOI: 10.1080/02102412.2003.10779479
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Disclosure in Spain: Corporate Characteristics and Media Exposure

Abstract: Social

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
27

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 32 publications
4
32
0
27
Order By: Relevance
“…The author, who analysed all IBEX 35 companies, considers that the variables that have the greatest influence on CSR are a company's media exposure, followed by its size, and the industrial sector to which it belongs. As mentioned by the author, many studies have found a positive relationship between CSR and business performance (Belkaoui & Karpik, 1989;Cowen, Ferreri & Parker, 1987;Ismail & Chandler, 2005;Roberts, 1992;Ullmann, 1985), although some empirical studies do not confirm this positive relationship (Archel, 2003;Brammer & Pavelin, 2008;Carmona & Carrasco, 1988;García-Ayuso & Larrinaga, 2003;Moneva & Llena, 1996). Therefore, we can conclude that there is no consensus on the relationship between C SR and business results.…”
Section: Csr and Business Resultsmentioning
confidence: 99%
“…The author, who analysed all IBEX 35 companies, considers that the variables that have the greatest influence on CSR are a company's media exposure, followed by its size, and the industrial sector to which it belongs. As mentioned by the author, many studies have found a positive relationship between CSR and business performance (Belkaoui & Karpik, 1989;Cowen, Ferreri & Parker, 1987;Ismail & Chandler, 2005;Roberts, 1992;Ullmann, 1985), although some empirical studies do not confirm this positive relationship (Archel, 2003;Brammer & Pavelin, 2008;Carmona & Carrasco, 1988;García-Ayuso & Larrinaga, 2003;Moneva & Llena, 1996). Therefore, we can conclude that there is no consensus on the relationship between C SR and business results.…”
Section: Csr and Business Resultsmentioning
confidence: 99%
“…El sector al que se pertenece [Hackston y Milne, 1996; Ness y Mirza 1991; Deegan y Gordon 1996; García-Ayuso y Larrinaga, 2003]; el carácter pú-blico o privado de la propiedad de las firmas [Cormier y Gordon, 2001]; la rentabilidad y el endeudamiento [Belkaoui y Karpick 1989]; el riesgo sistemático [Trotman y Bradley, 1981]; o el país de origen de los propietarios [Adams y otros, 1998], entre otros, han sido considerados aspectos relacionados con la cantidad de información social y/o medioambiental revelada. Por esta razón, en aras siempre a dar validez interna a los «constructos» y tomando como referencia a la literatura previa, se introducirán en el análisis tres variables más.…”
Section: El Uso De La Contabilidad Como Herramienta Estratégica De Leunclassified
“…En primer lugar, su introducción en la muestra hubiera hecho difícil la comparación de este estudio con la literatura previa. La mayoría de los trabajos en el contexto internacional no las han investigado y, debido a su escaso impacto medioambiental, los trabajos españoles más relevantes también las han excluido del análisis [ver Moneva y Llena, 1996Archel y Lizarraga, 2001; Larrinaga y otros, 2002; García-Ayuso y Larrinaga, 2003;Archel, 2003]. En segundo lugar, la inclusión de este sector elevaría artificialmente las correlaciones objeto de estudio debido a que su insignificante impacto directo en el medio ambiente (que conllevaría que no hubiese apenas noticias en prensa ni información revelada por las firmas) menoscabaría la robustez del análisis.…”
Section: Elección De La Muestraunclassified
See 2 more Smart Citations